Digital dalam rangka Mendorong Pertumbuhan Ekonomi Lokal - Candra Khoirul Umam; RM Syah Arief Atmaja Wijaya (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Digital innovation has always been a major milestone in advancing the economy of MSMEs from local to national scale, especially in Wonomerto Village. Through participatory observation, students were present directly to explore MSMEs in Wonomerto Village in utilizing technology to expand market access and operational efficiency. The results prove the positive impact of using digital technology in increasing marketing reach, catalyzing business processes, which is ultimately connected to increased income. What needs to be highlighted is how barriers such as limited knowledge of technology in the village community threaten data security and reduce the level of community acceptance. The program not only educates the community on digital innovation, but also focuses on other sectors in order to increase sustainable economic growth in the village ecosystem.